2016
DOI: 10.1016/j.mseb.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Condensed phase diagrams for the metal–W–S systems and their relevance for contacts to WS2

Abstract: Motivated by interest in contacts to the layered semiconductor WS 2 , this study investigates condensed phase equilibria in M-W-S systems (M = transition or post-transition metal) and relates the findings to earlier work on M-Mo-W systems. Thermodynamic data were collected or estimated for the binary phases bearing M, W, and/or S; and a literature search for existing ternary phases was performed.Condensed phase M-W-S isothermal phase diagrams were calculated where sufficient data was available.These phase diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
3
4
0
Order By: Relevance
“…In general, WTe 2 is the most reactive tungsten dichalcogenide followed by WSe 2 and WS 2 . This work shows that the interface chemistry at a metal−TMD interface can be roughly predicted by considering the thermodynamics of the metal− TMD system and provides experimental support for previous thermodynamic calculations of equilibrium phases in metal− tungsten dichalcogenide systems 58 (provided the metal is deposited under a pressure that is <1 × 10 −8 mbar). The abundance of background gases in an elastomer-sealed deposition tool (base pressure ∼1 × 10 −6 mbar) complicates the reaction thermodynamics during metallization, which should be considered when evaluating the performance of more reactive contact metals.…”
Section: ■ Methodssupporting
confidence: 78%
“…In general, WTe 2 is the most reactive tungsten dichalcogenide followed by WSe 2 and WS 2 . This work shows that the interface chemistry at a metal−TMD interface can be roughly predicted by considering the thermodynamics of the metal− TMD system and provides experimental support for previous thermodynamic calculations of equilibrium phases in metal− tungsten dichalcogenide systems 58 (provided the metal is deposited under a pressure that is <1 × 10 −8 mbar). The abundance of background gases in an elastomer-sealed deposition tool (base pressure ∼1 × 10 −6 mbar) complicates the reaction thermodynamics during metallization, which should be considered when evaluating the performance of more reactive contact metals.…”
Section: ■ Methodssupporting
confidence: 78%
“…The persistence of multiple Raman active modes even after metallization and annealing up to 300 ºC and mechanical exfoliation means that Cu remains unreactive with WS2 at room temperature and with annealing. Ternary phase diagrams calculated by Zeng et al show equilibrium between bulk WS2 and Cu at room temperature 23 , and x-ray diffraction studies have indicated no reactivity between bulk WS2 and Cu below 850 o C 33 , consistent with our findings for 1L WS2.…”
Section: Coppersupporting
confidence: 92%
“…into three reactivity groups: metal-sulfide dominant (reactive), WS2 dominant (unreactive), and ternary/solid solution dominant (Figure 1), 23 similar to the study by Domask et al on metal/MoS2 systems 24 . In our current study, reactions between metals and WS2 can be correlated with changes in the Raman spectrum upon metallization and annealing.…”
Section: Phase Diagram Calculations By Zeng Et Al Categorize Transiti...supporting
confidence: 83%
See 2 more Smart Citations